Local Wisdom as Learning Innovation in Elementary SchoolsLocal Wisdom as Learning Innovation in Elementary Schools - Laelia Nurpratiwiningsih; Rusdarti Rusdarti; Joko Widodo; Tjaturahono Budi Sanjoto (International Conference on Science, Education, and Technology, 2023)
Local wisdom is a rich and unique cultural heritage owned by the people. However, this local wisdom has not been fully utilized as a learning innovation in elementary schools. This study aims to understand how local wisdom can be used as learning innovation in elementary schools. This study uses a qualitative approach with data collection techniques through in-depth interviews and participatory observation. The results of the study show that local wisdom can be used as learning innovation in elementary schools in various aspects, such as in learning languages, arts and sciences. Learning local wisdom can increase students' interest in learning and enrich their learning experience. In addition, learning local wisdom can also strengthen students' cultural identity and promote local wisdom to the younger generation. However, there are also challenges in implementing local wisdom learning in elementary schools, such as the lack of resources and support from the school and the government. Therefore, greater efforts are needed from the school, government and community to promote and integrate local wisdom as a learning innovation in elementary schools.